GATA4, 5 and 6 mediate TGFbeta maintenance of endodermal gene expression in Xenopus embryos. - Afouda, B; Ciau-Uitz, A; Patient, R (2005)
The individual contributions of the three vertebrate GATA factors to endoderm formation have been unclear. Here we detail the early expression of GATA4, 5 and 6 in presumptive endoderm in Xenopus embryos and their induction of endodermal markers in presumptive ectoderm. Induction of HNF3beta by all three GATA factors was abolished when protein synthesis was inhibited, showing that these inductions are indirect. In contrast, whereas induction of Sox17alpha and HNF1beta by GATA4 and 5 was substantially reduced when protein synthesis was inhibited, induction by GATA6 was minimally affected, suggesting that GATA6 is a direct activator of these early endodermal genes. GATA4 induced GATA6 expression in the same assay and antisense morpholino oligonucleotides (MOs), designed to knock down translation of GATA6, blocked induction of Sox17alpha and HNF1beta by GATA4, suggesting that GATA4 induces these genes via GATA6 in this assay. All three GATA factors were induced by activin, although GATA4 and 6 required lower concentrations. GATA MOs inhibited Sox17alpha and HNF1beta induction by activin at low and high concentrations in the order: GATA6>GATA4>GATA5. Together with the timing of their expression and the effects of GATA MOs in vivo, these observations identify GATA6 as the predominant GATA factor in the maintenance of endodermal gene expression by TGFbeta signaling in gastrulating embryos. In addition, examination of gene expression and morphology in later embryos, revealed GATA5 and 6 as the most critical for the development of the gut and the liver.